Assembly of soil multitrophic community regulates multifunctionality via multifaceted biotic factors in subtropical ecosystems - Chao Chang; En Hu; Xiaofeng Tang; Sisi Ye; Dan Zhao; Zhi Qu; Ming Li (Environment International)
Soil biodiversity underpins multiple ecosystem functions and services essential for human well-being. Understanding the determinants of biodiversity-ecosystem function relationships (BEFr) is critical for the conservation and management of soil ecosystems. Community assembly processes determine community diversity and structure. However, there remains limited systematic research on how the assembly processes of multiple organismal groups affect soil ecosystem functions through their influence on biodiversity and species interactions. Here, we analyzed 331 soil samples from different land-use types (cropland, forest, and grassland) in the Qinling-Daba Mountains to investigate the drivers, assembly processes, and network stability of multitrophic organisms. High-throughput sequencing was used to examine archaea, bacteria, fungi, algae, protozoa, and invertebrates, while enzyme activity assays were used to assess ecosystem multifunctionality related to nutrient provisioning. Our results indicated that biotic factors contributed to 62.81–94.97 % of α-diversity and 4.19–52.37 % of β-diversity in multitrophic organisms, even when considering the influence of abiotic factors. Protozoan α- and β-diversity most significantly explained the α- and β-diversity of bacteria, fungi, algae, and invertebrates in soil ecosystems, serving as important indicators for assessing soil multifunctionality and ecosystem health. Furthermore, the assembly processes in prokaryotes were primarily governed by stochasticity (>50 %), whereas those in eukaryotic groups were dominated by deterministic processes (<50 %). Diversity and network stability increased with greater stochasticity in bacterial communities where stochastic processes predominated. Conversely, in fungal and protozoan communities dominated by deterministic processes, diversity and network stability decreased as deterministic processes intensified. Importantly, stochastic processes in soil multitrophic assembly enhanced ecosystem multifunctionality by increasing α-diversity, β-diversity, and network stability. These findings provide valuable insights into the regulation of BEFr by multitrophic assembly processes. Future research should further explore the role of these assembly processes in soil ecosystem functioning under land-use change scenarios.